The Unapologetic Mathematician

Mathematics for the interested outsider

Inverses of Power Series

Now that we know how to compose power series, we can invert them. But against expectations I’m talking about multiplicative inverses instead of compositional ones.

More specifically, say we have a power series expansion

\displaystyle p(x)=\sum\limits_{n=0}^\infty p_nz^n

within the radius r, and such that p(0)=p_0\neq0. Then there is some radius \delta within which the reciprocal has a power series expansion

\displaystyle\frac{1}{p(x)}=\sum\limits_{n=0}^\infty q_nz^n

In particular, we have q_0=\frac{1}{p_0}.

In the proof we may assume that p_0=1 — we can just divide the series through by p_0 — and so p(0)=1. We can set

\displaystyle P(z)=1+\sum\limits_{n=1}^\infty\left|p_nz^n\right|

within the radius h. Since we know that P(0)=1, continuity tells us that there’s \delta so that |z|<\delta implies |P(z)-1|<1.

Now we set

\displaystyle f(z)=\frac{1}{1-z}=\sum\limits_{n=0}^\infty z^n
\displaystyle g(z)=1-p(z)=\sum\limits_{n=0}^\infty -p_nz^n

And then we can find a power series expansion of f\left(g(z)\right)=\frac{1}{p(z)}.

It’s interesting to note that you might expect a reciprocal formula to follow from the multiplication formula. Set the product of p(z) and an undetermined q(z) to the power series 1+0z+0z^2+..., and get an infinite sequence of algebraic conditions determining q_n in terms of the p_i. Showing that these can all be solved is possible, but it’s easier to come around the side like this.


September 24, 2008 - Posted by | Analysis, Calculus, Power Series

No comments yet.

Leave a Reply

Fill in your details below or click an icon to log in: Logo

You are commenting using your account. Log Out /  Change )

Google+ photo

You are commenting using your Google+ account. Log Out /  Change )

Twitter picture

You are commenting using your Twitter account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )


Connecting to %s

%d bloggers like this: